Struktura povezanosti izbranih kinematičnih spremenljivk in dolžine poletov na tekmovanjih za svetovni pokal - Jošt, Bojan (Šport (Ljubljana), 2016)
Ski jumping is an attractive winter sport which always gathers huge spectator numbers. One of the venues for interesting ski jumping events at the end of individual seasons is the Bratov Gorišek ski jump in Planica. The study aimed to examine the structure of selected kinematic factors of the ski jumping technique (run-up velocity, flight height at the 112 m point, aerodynamic index of the flight at the 112 m point, FIS points for wind speed and direction) mainly in terms of their correlation with the length of ski jumps. The research included the best ski jumpers who took part in four ski jumping competitive series in individual competitions in Planica in 2009, 2010 and 2013. The results showed considerable variability of the basic statistical results in terms of individual independent variables and ski jumping series. The flight height at the 112 m point was greatest during the afternoon competition in 2013 when ski jumpers used the smallest size competition suits (+2 cm). This contributed to large angles of incidence in the landing phase and higher pressures on contact with the ground. Consequently, the International Ski Federation allowed the use of larger competition suits (up to +4 cm) the next year, i.e. in the 2013/2014 season. The variable of flight height was generally highly statistically significantly correlated with the flight length (p < 0.05). In individual series of jumps at the 2013 competition, during the last final round, a significant correlation between the variable of the FIS points for wind and the flight length (r = 0.51** and r = 0.66**) was established in both series.
Keywords: competition suits; kinematics; kinematika; ski jumping; smučarski skoki; sport; svetovni pokal; šport; tekmovalni dresi